2023
DOI: 10.1093/braincomms/fcad208
|View full text |Cite
|
Sign up to set email alerts
|

RFC1 in an Australasian neurological disease cohort: extending the genetic heterogeneity and implications for diagnostics

Abstract: Cerebellar ataxia, neuropathy and vestibular areflexia syndrome (CANVAS) is a progressive, generally late-onset, neurological disorder associated with biallelic pentanucleotide expansions in intron 2 of the RFC1 gene. The locus exhibits substantial genetic variability, with multiple pathogenic and benign pentanucleotide repeat alleles previously identified. To determine the contribution of pathogenic RFC1 expansions to neurological disease within an Australasian cohort and further investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
2
4
0
Order By: Relevance
“…We hereby report our current findings, including the diagnosis of 10 homozygous patients for the pathogenic AAGGG expansion and the high percentage of heterozygous AAGGG carriers both in the group of patients and controls. We also report the identification of 2 of the recently reported novel benign repeat configurations AAAGGG n and AAGAC n , 8 , 9 thus confirming their existence in another distinct population, and we highlight an increased frequency of the hexanucleotide AAAGGG n in the patient group.…”
Section: Introductionsupporting
confidence: 78%
See 4 more Smart Citations
“…We hereby report our current findings, including the diagnosis of 10 homozygous patients for the pathogenic AAGGG expansion and the high percentage of heterozygous AAGGG carriers both in the group of patients and controls. We also report the identification of 2 of the recently reported novel benign repeat configurations AAAGGG n and AAGAC n , 8 , 9 thus confirming their existence in another distinct population, and we highlight an increased frequency of the hexanucleotide AAAGGG n in the patient group.…”
Section: Introductionsupporting
confidence: 78%
“…This repeat has been reported only in compound heterozygosity with the AAGGG or other non-pathogenic expansions. 8 , 9 Homozygosity in a single patient presenting with ataxia and neuropathy is reported for the first time in the current study. Furthermore, compared with Dominik et al (2023), who found a similar frequency of the compound heterozygotes AAGGG/AAAGGG in patients (0.6%) and controls (0.4%), we identified 3 compound heterozygous AAGGG/AAAGGG patients (1.6%) and none in the controls (0%).…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations